Pharmacokinetics of enrofloxacin following intravenous administration to greater rheas: A preliminary study - de Lucas, José Julio (2005)
The pharmacokinetic behaviour of enrofloxacin (ENR) and its active metabolite ciprofloxacin (CIP) were determined in six greater rheas following a single intravenous (i.v.) dose of 15 mg/kg bw. Plasma concentrations of ENR and CIP were simultaneously determined by a HPLC/u.v. method. Following i.v. administration, the plasma drug concentrations were best fitted by an open two-compartment model with a rapid distribution phase. The high volume of distribution (Vss = 5.01 L/Kg) suggests good tissue penetration. ENR presents a high clearance (3.95 L/kg h) explaining the low AUC values (3.57 mg h/L) and a short permanence (t1/2β = 2.66 h and MRT = 1.23 h). Ciprofloxacin comprised 14% of the total fluoroquinolone (ENR + CIP).